The Effect of System Security and User Trust on Online Transaction Decisions in E Commerce - Bambang Winardi; ZM, Ajub Ajulian; Sinuraya, Enda Wista (Westscience Press, 2026)
This study aims to analyze the influence of system security and user trust on online transaction decisions in e-commerce in Indonesia. A quantitative research approach was employed, with data collected from 75 respondents using a structured questionnaire based on a Likert scale. The sampling technique used was purposive sampling, targeting individuals who have experience in conducting online transactions. Data were analyzed using SPSS version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that system security and user trust have a positive and significant effect on online transaction decisions, both partially and simultaneously. System security also has a significant effect on user trust, indicating its role as a fundamental factor in building consumer confidence. The regression analysis reveals that system security and user trust significantly influence transaction decisions, with an adjusted R² value of 0.491. This indicates that 49.1% of the variation in online transaction decisions can be explained by the two variables. The findings suggest that enhancing security systems and strengthening user trust are essential strategies for e-commerce platforms to improve consumer participation and transaction behavior in Indonesia.